An Assessment of the Bivalve Perna viridis, as an Indicator of Heavy Metal Contamination in Paradise Point of Karachi, Pakistan: Heavy Metals Concentration in Perna viridis - Qari, Rashida; Ajiboye, Olufemi; Imran, Saima; Afridi, Abdul Rahim (Biological Sciences - PJSIR, 2016)
The edible bivalves Perna viridis (green mussel), (n = 100) were analysed for their total Hg, Pb, Cu, Ni, Zn, Co, Fe, Cr, Cd, and Mn concentrations to indicate heavy metal contamination in Paradise Point of Karachi coast using atomic absorption spectrophotometer. There are large seasonal variations in the metal concentrations of Mn (0.025-0.67 µg/g), Fe (0.055-7.740 µg/g), Ni (0.004-0.52 µg/g), Hg (0.0001- 0.004 µg/g), Zn (0.04-3.32 µg/g), Cu (0.008-1.66 µg/g), Pb (0.022-2.43 µg/g), Co (0.01-0.044 µg/g), Cd (0.04-0.88 µg/g) and Cr (0.13-1.20 µg/g) recorded in bodies/soft tissues of P. viridis obtained in the samples of the year 1993 and 2012 at the Paradise Point of Karachi coast. The results of heavy metals are in the following descending order of concentration in the samples collected in the year 1993: Fe>Cr>Zn>Mn> Pb>Cd>Cu>Ni>Co>Hg, while Fe>Zn>Pb>Cu>Cr>Cd>Mn>Ni>Co>Hg order was recorded in samples collected in the year 2012. The high accumulation of metals was found mostly in the samples collected in the year 2012 when compared with the samples of the year 1993. This is an indication that the area under study showed signs of being exposed to significant levels of heavy metal pollution due to direct discharge of industrial and domestic wastes along the coast. The concentrations of these heavy metals were lower than the permissible limits for human consumption. However, if this pollution persists, it can prove to be very detrimental in future.